Japanese foreign intelligence and grand strategy from the cold war to the Abe era - Williams, Brad, 1969- (Georgetown University Press, 2021)
Incisive insights into the distinctive nature of Japanese foreign intelligence and grand strategy, its underlying norms, and how they have changed overtime.